Diversity of methicillin-resistant Staphylococcus aureus CC22-MRSA-IV from Saudi Arabia and the Gulf region. (October 2016) - Senok, Abiola; Somily, Ali; Raji, Adeola; Gawlik, Darius; Al-Shahrani, Fatimah; Baqi, Shehla; Boswihi, Samar; Skakni, Leila; Udo, Edet E.; Weber, Stefan; Ehricht, Ralf; Monecke, Stefan
Highlights: This article describes a methicillin-resistant Staphylococcus aureus (MRSA) isolate from Riyadh, Kingdom of Saudi Arabia, which was originally thought to belong to the pandemic UK-EMRSA-15/Barnim epidemic strain. More detailed characterization showed it to harbour a different SCC mec element. Further investigations on CC22 MRSA strains showed a parallel presence of as many as six distinct CC22 MRSA strains in the Arabian Gulf region. However, the original UK-EMRSA-15/Barnim epidemic strain, sensu strictu, was not found in the Kingdom of Saudi Arabia. It was identified in other countries in this region. Summary: Objectives: CC22-MRSA-IV, UK-EMRSA-15/Barnim EMRSA, is a common and pandemic strain of methicillin-resistant Staphylococcus aureus (MRSA) that has been found mainly in Western Europe, but also in other parts of the world including some Gulf countries. One suspected case of an infection with this strain in a patient who was admitted to the surgical unit in Riyadh, Kingdom of Saudi Arabia (KSA) was investigated in order to check whether this strain has reached KSA. Methods: Besides the index isolate, 46 additional isolates of CC22-MRSA-IV from patients from KSA, Abu Dhabi, Kuwait, and Germany (patients with a history of travel in the Middle East), were characterized by microarray hybridization. Results: The study revealed a regional presence of as many as six distinct 'strains' of CC22-MRSA-IV that could be distinguished based on carriage of SCC mec IV subtypes and virulence factors. No true UK-EMRSA-15/Barnim EMRSA was identified in Riyadh; all suspected isolates from Riyadh were assigned to other, albeit related strains. However, this strain was identified in Abu Dhabi and Kuwait. Conclusions: CC22-MRSA-IV from KSA could be linked to other epidemic strains from the Middle East and possibly India, rather than to the Western European UK-EMRSA-15/Barnim EMRSA. High-resolution typing methods, including SCC mec subtyping, might help to differentiate related epidemic strains and to monitor routes of transmission.